Aldo-keto Reductase Metabolizes Glyphosate and Confers Glyphosate Resistance in Echinochloa colona. Issue 4 (24th September 2019) - Pan, Lang; Yu, Qin; Han, Heping; Mao, Lingfeng; Nyporko, Alex; Fan, LongJiang; Bai, Lianyang; Powles, Stephen
Abstract : The plant metabolic enzyme aldo-keto reductase has evolved to metabolize glyphosate in a glyphosate-resistant weed species Abstract: Glyphosate, the most commonly used herbicide in the world, controls a wide range of plant species, mainly because plants have little capacity to metabolize (detoxify) glyphosate. Massive glyphosate use has led to world-wide evolution of glyphosate-resistant (GR) weed species, including the economically damaging grass weed Echinochloa colona . An Australian population of E . colona has evolved resistance to glyphosate with unknown mechanisms that do not involve the glyphosate target enzyme 5-enolpyruvylshikimate-3-P synthase. GR and glyphosate-susceptible (S) lines were isolated from this population and used for resistance gene discovery. RNA sequencing analysis and phenotype/genotype validation experiments revealed that one aldo-keto reductase (AKR) contig had higher expression and higher resultant AKR activity in GR than S plants. Two full-length AKR ( EcAKR4 - 1 and EcAKR4 - 2 ) complementary DNA transcripts were cloned with identical sequences between the GR and S plants but were upregulated in the GR plants. Rice ( Oryza sativa ) calli and seedlings overexpressing EcAKR4 - 1 and displaying increased AKR activity were resistant to glyphosate. EcAKR4-1 expressed in Escherichia coli can metabolize glyphosate to produce aminomethylphosphonic acid and glyoxylate. Consistent with these results, GR E . colona plants exhibited enhanced capacity for detoxifying glyphosate into aminomethylphosphonic acid and glyoxylate. Structural modeling predicted that glyphosate binds to EcAKR4-1 for oxidation, and metabolomics analysis of EcAKR4 - 1 transgenic rice seedlings revealed possible redox pathways involved in glyphosate metabolism. Our study provides direct experimental evidence of the evolution of a plant AKR that metabolizes glyphosate and thereby confers glyphosate resistance.